Selection of new design gas carriers by using fuzzy EVAMIX method - Devran Yazır; Bekir Şahin; Tsz Leung Yip (Asian Journal of Shipping and Logistics (AJSL), 2021)
This paper extends the EVAMIX (EVAluation of MIXed Data) as an exemplary multi-criteria decision-making method in three perspectives. First, the problem is investigated in a fuzzy environment. Secondly, multiple decision-makers involve in decision-making process. It allows the moderator to benefit the opinions of multiple experts. Third, experts are assigned a coefficient considering their professional career represented in years. In the conventional approach, the experts have assumed identical, but expert prioritization deals with the instability. The extensions applied in this study are currently available in the literature, and it is used for the first time in the EVAMIX method. This method can be applied to decision-making problems in any research field. A study is carried out to combine the pre-determined types of ships with reliable quantitative and qualitative criteria and create data for new investors and shipowners in the selection of ships using a novel mathematical approach. As a result of the study, preferences are modelled for candidate ships, and database and value options are presented to decision-makers, ship owners, and investors. The qualitative and quantitative data discussed in this selection process to support the decision-making process and can be designed appropriately to be used in similar selection problems. The most suitable vessel to be selected from the candidate's vessels is carried out based on the existing criteria being evaluated; therefore, it is a reference for similar methodologies.
Keywords: 650; Shipping industry; Decision-making; EVAMIX; Fuzzy sets; Expert systems